Ferulic Acid against Cyclophosphamide-Induced Heart Toxicity in Mice by Inhibiting NF-κB Pathway. (4th January 2016) - Song, Yafan; Zhang, Chunyan; Wang, Congxia; Zhao, Ling; Wang, Zheng; Dai, Zhijun; Lin, Shuai; Kang, Huafeng; Ma, Xiaobin
Abstract : The purpose of the present study was to elucidate the protective effects of ferulic acid (FA) against cyclophosphamide- (CTX-) induced changes in mice. Forty-eight male ICR mice were divided into four groups. Control group was intraperitoneally (i.p.) injected with 200 μ L of phosphate buffer saline (PBS). Model group was intraperitoneally injected with a single dose of CTX (200 mg/kg). FA (50 mg/kg) and FA (100 mg/kg) groups were intraperitoneally injected with a single dose of CTX (200 mg/kg) followed by the intragastric treatment with FA (50, 100 mg/kg) for 7 consecutive days. After 12 d, the mice were sacrificed to analyze the hematological, biochemical, histological parameters and mechanism research. The results indicated that FA significantly decreased the serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), creatine kinase (CK), lactate dehydrogenase (LDH), interleukin-6 (IL-6), IL-1 β, and tumor necrosis factor- α (TNF- α ) in CTX-injected mice. In addition, FA effectively reduced the total numbers of white blood cells (WBCs), red blood cells, platelets, and hemoglobin content. FA also obviously attenuated the histological changes of the heart tissues caused by CTX. Moreover, Western blot demonstrated that FA inhibited the phosphorylations of NF- κ B signaling pathway in CTX-stimulated cardiac tissues. In conclusion, FA might be considered as an effective agent in the amelioration of the heart toxicity resulting from CTX treatment.